A Streamlining USAID IUWASH-Jawa Barat: Kolaborasi Sustainable Development Goals dalam Infrastruktur Air Bersih dan Sanitasi: Global Political Economic - Reza Aulia Rakhman (Global Local Interactions: Journal of International Relations, 2023)
USAID IUWASH Tangguh-West Java is a big momentum in achieve the Sustainable Development Goals. This emphasizes the issue of extreme climate change such as drought which has an impact on the lack of availability of clean drinking water and sanitation. This project aims to enhance partnerships, provide technical assistance to the Government of Indonesia, the private sector to the community. The writing method used is descriptive research (literature study) based on electronic scientific publications (journals and books), publications on the USAID IUWASH website and the Government of West Java, monitoring and evaluation reports. While the conceptual framework in the analysis will use the Streamlining NGO's Programs Towards Achieving the SDGs Concept owned by Mohamad, Khai, and Mazlin (2018). This concept has a two-mechanism approach, namely cross-sector partnerships and the expansion of social values. Keywords : Sustainable Development Goals, USAID IUWASH, Foreign Aid, Water Supply and Sanitation Development Project, Development Studies